Pendampingan dan Pemulihan Pasca Erupsi Gunung Ruang dengan Kegiatan Kreatif Ikebana pada Masyarakat Tagulandang - Sompotan, Amelia G.Y; Lensun, Sherly F (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2024)
The purpose of this service activity is to provide assistance to the community, especially the Tagulandang village community who experienced the mountain eruption disaster with the inte-gration of creative activities in the Japanese art of Ikebana. Ikébana (生花) is the art of flower arrangement that utilizes various types of flowers, grasses and plants with the aim of enjoying their beauty. The results of this service activity have a good impact on the community, especially for (1) restoring their mental health, the art of Ikebana is not just arranging flowers but this art is able to relax and refresh the brain and balance the needs of the body. (2) Fostering resilience and spirit so that they feel that their burden is lessened and they can continue their lives with re-newed vigor.